Population structure and exploitation rate of striped snakehead (Channa striata) in Kawunganten Swamp, Cilacap, Indonesia: Important for fisheries management - NUNING SETYANINGRUM; SUGIHARTO SUGIHARTO; PRIYO SUSATYO (Society for Indonesian Biodiversity, 2024)
Abstract. Setyaningrum N, Sugiharto, Susatyo P. 2024. Population structure and exploitation rate of striped snakehead (Channa striata) in Kawunganten Swamp, Cilacap, Indonesia: Important for fisheries management. Biodiversitas 25: 3255-3263. Snakehead (Channa striata) is a swamp fish spread in almost all Indonesian waters and has a high economic value. In addition, Bringkeng, Grugu, and Babakan Villages are included in Kawunganten Swamp areas with good fishing potential. Therefore, this study aimed to determine the population structure and the exploitation rate of Channa striata in Kawunganten Swamp Cilacap, Indonesia. The survey method with purposive random sampling was used and this study was conducted from April to July 2020. The fish samples were collected from three Bringkeng, Grugu, and Babakan Swamp stations, while the variables examined were abundance and rate of exploitation. The parameters measured included the length of Channa striata as well as the growth and mortality rate in each swamp. Abundance was analyzed using the Kruskal-Wallis test, and exploitation rate was assessed with Pauly's model using FAO-ICLARM Stock Assessment Tools II (FISAT II). The results showed that the highest abundance of Channa striata was in Bringkeng station, three times higher than in Babakan station. Bringkeng and Babakan stations were considered a fish-rearing swamp due to the dominance of adolescence-sized samples. Grugu was identified as the breeding area because many of the fish present were in the reproductive phase. Estimated growth parameters showed a maximum length (L?) of 35.18 cm, while exploitation rate of 0.28 was not considered excessive capture. Efforts to manage Channa striata were important to preserving biodiversity and ensuring the sustainability of Kawunganten Swamp ecosystem for future generations.